Medicine Identification for Blind People by Deep Learning Techniques - Ch Mary; M. Supriya; V. Nishanth; G. Divya; MD. Apsar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Giving blind people with great accessibility to their environment is of great demand. People with visual impairments experience a lot of problem in using the modern assistive device that limits their daily basic activities. The level of assistance provided of these special aids does not meet the consumer requirements and not affordable by the every section of the society. To overcome the some of the limitations of the existing visual aids, in this paper we present the work that helps the visually impaired person with smart glasses to identify the medicine. The name of the medicine can be read by the smart glass system that provides audio signal through the ear phones. The smart glass system reads the medicine name using Convolutional neural network.